Alterations in plasma cytokine profiles in generalized myasthenia gravis following different immunotherapeutic regimens - Ren, Zhuangzhuang; Ma, Xihui; Liu, Yudan; Zhang, Yufeng; Chen, Yuping; Sun, Chenjing; Qiu, Feng (Frontiers in Neurology, 2025)
BackgroundThe pathogenesis of myasthenia gravis (MG) involves an imbalance of various pro-inflammatory and anti-inflammatory cytokines. Currently, there are no clinical studies comparing the effects of hormones and different non-hormonal immunosuppressants on the regulation of plasma cytokines. Hence, there is no unified standard for drug selection. This study aims to explore the associations between glucocorticoid (GC), tacrolimus (TAC), and rituximab (RTX) and plasma cytokine levels in generalized myasthenia gravis, providing an observational overview of how different treatment regimens relate to immune-inflammatory patterns in clinical practice.MethodsA retrospective collection of 65 GMG patients diagnosed at the Department of Neurology, General Hospital of the People’s Liberation Army from July 2022 to May 2024 was conducted. According to treatment regimens, patients were divided into a GC group (n = 17), a TAC group (n = 17), a RTX group (n = 9), and non-medicated patients (NM) group (n = 22), another 30 healthy individuals were selected as the healthy control (HC) group. Clinical data and levels of cytokines such as Interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12P70, IL-17, Tumor Necrosis Factor (TNF)-α, Interferon (IFN)-α, and IFN-γ in plasma were collected to compare plasma cytokine levels across the three treatment groups and the non-medicated group.ResultsCompared with the HC group, GMG patients in the NM group showed significantly higher plasma levels of IL-1β, IL-2, IL-4, IL-10, IL-17, TNF-α, IFN-α, and IFN-γ. Relative to the NM group, the GC group exhibited lower levels of IL-1β, IL-4, IL-6, IL-17, and TNF-α, and the RTX group showed lower levels of IL-1β, IL-4, IL-6, IFN-α, and TNF-α. In the comparison across treatment groups, the GC group presented lower IL-17 and IFN-γ levels than the TAC group, while the RTX group presented lower IL-6, IFN-α, and TNF-α levels than the TAC group.ConclusionCytokine levels were markedly elevated in the plasma of patients with GMG, indicating their potential involvement in disease-related immune dysregulation. Distinct treatment groups displayed different cytokine patterns, reflecting heterogeneous immunological states among patients receiving GC, TAC, or RTX. Collectively, these findings provide preliminary immunological insights into GMG and highlight the need for validation in larger, prospective studies.